Exploring Space Warfare: The Strategic Contest among US, Russia, and China for Dominance in Outer Space and its Role in Reshaping Fifth Generation Warfare - Khalid, Ayesha (Annals of Human and Social Sciences, 2025)
Space has emerged as a critical frontier due to its scientific, technological, and strategic significance, particularly since the mid-20th century. This research explores the geopolitical contest between the United States, Russia, and China, as they vie for dominance in outer space. With the United States currently leading in space capabilities, Russia and China are rapidly advancing their counter-space technologies to challenge U.S. military hegemony and reshape the international space order. The integration of space warfare with fifth-generation warfare signals a transformative shift, extending the competition for global supremacy beyond Earth’s boundaries. This study analyzes how space has become a battlefield for strategic dominance, redefining the dimensions of modern warfare. Drawing on Neo-Realism, Constructivism, and Technological Determinism, the research examines the strategic interplay among these powers and evaluates the implications of their space race in shaping the evolving landscape of fifthgeneration warfare.